The Role of Think Tanks in Actions for Defence Diplomacy. An Example of Poland - Sabina Olszyk (Polish Political Science Yearbook, 2022)
With the end of the 20th century, there was a change in the nature and methods of using military force in international politics. It led to the need to develop new cooperation methods between states and reorient military diplomacy into defence diplomacy. In the new reality, the group of entities influencing diplomatic activities has been expanded to include non-governmental entities, including think tanks. It raised questions about the role of expert centres in activities for defence diplomacy under Polish conditions, including shaping the international situation and shaping the state's defence policy. The following considerations are an attempt to answer this question. The analysis was based on the data obtained from a survey and information from the websites of fifteen Polish centres of expertise operating in international relations, political science, and security and defence.